THE IMPACT OF THE MOVEMENT METHOD IN MEMORIZING HADITH ON CHILDREN AGED 5-6 AT RA BAKTI INSANI IN MATARAM CITY IN THE 2023-2024 ACADEMIC YEAR - Sibernika Isna Salsabila (Sinar Lima, 2025)
This research was motivated by the researcher's concern when observing students using hadith to reprimand each other for inappropriate behavior, such as littering. The purpose of this study was to determine the implementation and ability of children to memorize hadith using the movement method, as well as the impact of the movement method on hadith memorization at RA Bakti Insani in Mataram City. This study used a qualitative, descriptive approach. Data collection techniques used were three methods: observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and verification. Data validity was checked through diligent observation and triangulation. The results of this study indicate that the implementation of the movement method in teaching hadith memorization at RA Bakti Insani Mataram was carried out through several stages: (1) preparation, (2) implementation, and (3) evaluation. The ability of children aged 5-6 years in memorizing hadith at RA Bakti Insani in Mataram City was very good and met the teacher's targets. The movement method for memorizing hadith for children aged 5-6 years at RA Bakti Insani in Mataram City has the following impacts: (1) it is easier for children to memorize (2) their physical motor skills are better developed (3) children become accustomed to applying hadith in their daily lives.